1996
DOI: 10.1002/(sici)1097-4636(199603)30:3<305::aid-jbm5>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Pillared-surface microstructure and soft-tissue implants: Effect of implant site and fixation

Abstract: Previous work with subcutaneous implants in a rat animal model has shown that pillarlike surface microstructure will reduce fibrosis and enhance blood vessel approximation to the implant surface when compared with nontextured controls. This study was designed to determine the effect of microtissue anatomy and implant site on the observed response, as well as the effect of implant fixation. The lateral posterior sites were found to contain a fat pad which produced a dramatically reduced fibrosis for the micro-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Numerous others have also reported that surface-textured implants (e.g., pillars, porous surfaces) exhibit a significantly thinner and less dense fibrous capsule. [56][57][58][59][60] The greatly increased surface area of these porous and pillared materials serves to reduce interfacial stresses at the tissue-implant interface by allowing the stresses to distribute over a much greater surface area. 58 Therefore, it is hypothesized that the body does not attempt to provide as much mechanical stabilization when forces are distributed, so capsules are thinner and less dense.…”
Section: Wound Healing and Foreign Body Responsementioning
confidence: 99%
See 3 more Smart Citations
“…Numerous others have also reported that surface-textured implants (e.g., pillars, porous surfaces) exhibit a significantly thinner and less dense fibrous capsule. [56][57][58][59][60] The greatly increased surface area of these porous and pillared materials serves to reduce interfacial stresses at the tissue-implant interface by allowing the stresses to distribute over a much greater surface area. 58 Therefore, it is hypothesized that the body does not attempt to provide as much mechanical stabilization when forces are distributed, so capsules are thinner and less dense.…”
Section: Wound Healing and Foreign Body Responsementioning
confidence: 99%
“…Surface microarchitecture (including microtopography, pillars, and porous coatings) is an area of abundant biomaterial research 14,58,60,102,103 and has been applied to glucose sensors. 4,19,20,43,50,104 It is known that materials of the exact same chemical composition can exhibit vastly different FBR depending on the surface microarchitecture.…”
Section: Surface Topographymentioning
confidence: 99%
See 2 more Smart Citations
“…The surface topography seems to be the predominant factor for the induced tissue response when altering both material and topography [30], [31]. Textured, especially porous surfaces are preferable when compared with plane ones [32]- [34]. In vitro studies on cell culturing have shown that cell adherence and viability increased using porous silicon compared with planar silicon [35].…”
Section: Tissue Reactions Evoked By Porous and Planementioning
confidence: 99%